THE EFFECT OF LIVE STREAMING AND MARKETING CONTENT ON BUYING INTEREST IN PARIS VARISHA HIJAB PRODUCTS ON TIKTOKSHOP AMONG GENERATION-Z IN BOGOR REGENCY - Nurhaliza; Vivi Ristanti (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effect of live streaming and content marketing on purchase intention of Paris Varisha hijab products on TikTok Shop among Generation Z in Bogor Regency. The rapid development of digital technology and the increasing use of social media, particularly TikTok, have significantly transformed consumer behavior in online shopping. This research employs a quantitative approach using a survey method by distributing questionnaires to 100 respondents categorized as Generation Z. The sampling technique used is purposive sampling based on specific criteria. Data analysis to examine the relationships between variables. The results indicate that both live streaming and content marketing have a positive effect on purchase intention, both partially and simultaneously. Live streaming enhances interactive experiences and builds consumer trust, while content marketing attracts attention through creative and relevant content. Therefore, the combination of these two strategies is effective in increasing consumer purchase intention on the TikTok Shop platform.